Vascular Parkinsonism sensitive to Rotigotine therapy is found in aged patients: a clinical case description - Zarola, Flora (Acta Biomedica Atenei Parmensis, 2018)
Previous and recent papers have pointed out several discussions about the so called ‘Vascular Parkinsonism’ (VP), particularly about some distinctive characteristics with respect to the Idiopathic Parkinson Disease (IPD); differences commonly described are sudden onset of extrapyramidal symptoms after a stroke, main involvement of lower limbs in diffuse brain microinfarcts (lower body parkinsonism), low, short in time or absent response to classic IPD therapy in all kinds of vascular brain pathologies. But few published studies have also emphasized some relationship linking brain morphological signs of vascular damage in elder patients suffering from diagnosed IPD, both ‘normally’ responding to classic Levodopa therapy or not.